Searching for Better 3D Baseline Stimuli - Silva, Manuel (2020)
The use of accurate and appropriate physiological baseline procedures is essential in experimental paradigms in the field of neuroscience. However, the most challenging parts of designing a new study for experimental laboratory studies, especially when using psychophysiological measures, is the choice of the appropriate stimuli for the baseline or control task, in order to compute reactivity. This study aimed to select and validate the most suitable image category to be used as a baseline task, through self-report and physiological measures. The images were selected according to a previous baseline, but adding the 3D and virtual world component, which is the foundation of our experiment. An experiment comprising a number of visual stimuli (15 images) in a virtual world using a Virtual Reality system, in which we assessed valence and arousal through self-report measures after visualizing each stimulus. Our discussion will emphasize the challenges involved in choosing an appropriate type of stimuli for baseline tasks and suggest that caution is never wasted.